Estimating mine planning software utilization for decision-making strategies in the South African gold mining sector. - Genc, B.; Musingwini, C.; Celik, T. (The Southern African Institute of Mining and Metallurgy., 2015)
This paper discusses a new methodology for defining and measuring mine planning software utilization in the South African gold mining sector within an evolving data-set framework. An initial data-set showing the mine planning software providers, their corresponding software solutions, as well as the software capabilities and information on the number of licences was collected and compiled in 2012 in an online database for software utilized in the South African mining industry. Details of the database development and implementation were published in the Journal of the Southern African Institute of Mining and Metallurgy in 2013. In 2014 the data-set was updated with additional and new information. Using the 2012 and 2014 timestamps, a methodology for estimating the software utilization was developed. In this methodology, the three variables of commodity, functionality, and time factor were used to define and measure the software utilization in order to ultimately inform decision-making strategies for optimal software utilization. Using six different functionalities, namely Geological Data Management, Geological Modelling and Resource Estimation, Design and Layout, Scheduling, Financial Valuation, and Optimization, utilization in the gold sector was measured. This paper presents the methodology employed for measuring the mine planning software utilization. The methodology is useful for stakeholders reviewing existing software combinations or intending to purchase new software in the near future and who want to estimate the comparative attractiveness of a certain software package. These stakeholders include mining companies, consulting companies, educational institutions, and software providers. The work presented in this paper is part of a PhD research study in the School of Mining Engineering at the University of the Witwatersrand.
The work presented in this paper is part of a PhD research study in the School of Mining Engineering at the University of the Witwatersrand.
Keywords: Database; Gold sector; Mine planning software; Software utilization; South African mining industry; Decision making; Resource estimation; Information management; Gold mines